1997
DOI: 10.1002/(sici)1097-0339(199712)17:6<467::aid-dc17>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid cell aggregates: A useful clue in the fine-needle aspiration diagnosis of follicular lymphomas

Abstract: Among the various types of lymphoma, follicular lymphoma (FL) is known to have significant limitations in cytologic diagnosis by the fine‐needle aspiration (FNA) method. The diagnostic accuracy (DA) for non‐Hodgkin's lymphoma (NHL) by FNA was evaluated by review of 82 cases of histologically proved NHL after prior FNA. The DA for all NHLs was 66% (54/82), and that for low‐grade lymphomas, including small lymphocytic lymphoma, follicular small‐cleaved cell lymphoma, and follicular mixed cell lymphoma, was 71% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…An example is the recognition of FCFs in cases of FL initially reported by Suh et al [48], and their distinction from LHAs based on the presence of follicular dendritic cells alone in the former versus TBMs, follicular dendritic cells and activated cells in the latter. A stepwise approach as summarized in Table 1, which includes a low power assessment for cellularity, monomorphism, and predominant cell size with an astute examination for residual architectural features, that is, cell aggregates, followed by a detailed interrogation of the cytologic features at high power will yield the largest amount of information on which a tentative diagnosis can be built, and has the least potential to cause diagnostic confusion.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the recognition of FCFs in cases of FL initially reported by Suh et al [48], and their distinction from LHAs based on the presence of follicular dendritic cells alone in the former versus TBMs, follicular dendritic cells and activated cells in the latter. A stepwise approach as summarized in Table 1, which includes a low power assessment for cellularity, monomorphism, and predominant cell size with an astute examination for residual architectural features, that is, cell aggregates, followed by a detailed interrogation of the cytologic features at high power will yield the largest amount of information on which a tentative diagnosis can be built, and has the least potential to cause diagnostic confusion.…”
Section: Discussionmentioning
confidence: 99%
“…13,27,29 -33 Recently, Suh et al reported that cell aggregates were noted in 55% of FCLs. 34 However, 28% of diffuse large-cell lymphomas also demonstrated such cell aggregates. Furthermore, artifactual cell aggregates secondary to improper smear preparation may be difficult to distinguish from true aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…Suh et al reported recently that aggregation of uniform lymphoid cells is a relatively frequent finding in follicular lymphoma, whereas diffuse, small‐cleaved cell NHL lack this cytologic pattern 25. This observation could be supported by the immunocytochemical demonstration of an increased number of dendritic reticulum cells,26 which presumably may contribute to the adhesion of the individual lymphoma cells.…”
Section: Discussionmentioning
confidence: 92%